A cost effective solution for the deployment of wireless sensor networks. (18th February 2020) - D'Arienzo, M.; Romano, S.P.
The paper presents a framework for the design and implementation of dynamic sensor networks. The focus is on minimising the costs associated with deploying such networks, while at the same time making available a fully fledged set of functions. This is achieved by leveraging a modular design based on an easily programmable, cost-effective micro-controller that can be interfaced with a set of heterogeneous sensors and wireless technologies. A real-world implementation of the proposed architecture is described. Our preliminary in-field performance measurements show that such a system can manage, with a high degree of precision and in real-time, a sustained rate of data gathered from mobile units.